Determinants of retail outlet choice for fresh fruits and vegetables in Tagum City, Philippines - Lastimado, Russel Mae P.; Ramo, Glory Dee A.; Sarmiento, Jon Marx P.; Shuck, Vlademir A. (2016)
A continued dominance of traditional retail outlets is observed despite rapid modern retail expansion. To examine this trend in a predominantly agricultural area, a case study of Tagum City is conducted where developments in the retail food industry are presented and the determinants of retail outlet choice for fresh fruits and vegetables are identified. Multinomial and binary logit models were estimated to analyze the responses of 200 consumer-respondents among urban villages in Tagum City from 2011 to 2012. These were supplemented by key informant interviews. The results suggest that there is a potential for further expansion of the modern retail chain in Tagum City despite consumers' preference for traditional retail outlets. The top retail outlet attributes for fruit and vegetable buyers are convenience of location, price, product quality and speed of service. These findings have implications on consumer welfare, retail competition, and smallholder farmers.
Keywords: Retail stores; Fruits; Vegetables